Experimental demonstration of multi-watt wireless power transmission to ferrite-core receivers at 6.78 MHz. Issue 1 (11th December 2018) - Chyczewski, Stasiu; Hwangbo, Seahee; Yoon, Yong-Kyu; Arnold, David P.
Abstract : This article experimentally explores the use of ferrite cores to miniaturize the receivers used for inductive wireless power transmission. A variety of receivers were designed and fabricated using cylindrical ferrite cores, ranging in total size from 47 to 687 mm 3 . The receivers were tested with a commercially available transmitter operating under the Rezence (Air Fuel Alliance) standard at 6.78 MHz. Experiments measured performance of the receivers in terms of their maximum power draw and efficiency as functions of the receiver load and transmission distance. Experimental results showed that ferrite-core receivers could draw multiple watts of power with end-to-end efficiencies in excess of 50%. While the efficiencies are less than a commercially planar coil receiver, the ferrite-core receivers offer a >50% reduction in mass and >90% reduction in footprint. As a result, the receiver power densities reach up to 17.6 W/cm 3, which is a 25× improvement over previously reported work. This effort confirms the viability of ferrite-core receivers for size- and weight-constrained applications.